When we were saints - Nolan, Han. (Harcourt, 2003)
Inspired by his grandfather's last words and guided by a girl who believes they are saints, fourteen-year-old Archie sets out on a spiritual quest that takes him from southern Appalachia to the Cloisters Museum in New York City.